Maria silenciada: matrimônio e infidelidade conjugal em lares cristãos - Igreja, evento crítico e o refazimento do cotidiano pelo feminino de fé - Tomazelli, Ana Claudia da Costa Gomes (2024)
I could say that the present work aims to investigate the influence of religion – specifically the church as understood in the Brazilian evangelical field – on a woman's decision-making to maintain or dissolve her marriage after discovering marital infidelity promoted by her husband, in a formal relationship established as marriage, which would not be untrue. However, research itself has become bigger than we could imagine, like a self. So, taking advantage of the freedom of not being forced to enclose anything in itself, I declare that this work also proposes to discuss the subjectivity of this woman (the woman as a subject), not as someone passive, but as an agent who negotiates with religion , their attributes and promotions of responsibilities, as well as the structuring and/or particularized masculinities in the main actors (husband x pastor) to then delve into the concepts of family and their relationships with the church based on social constructions arising from reflected biblical readings in materials dedicated to the female gender. Finally, it is also possible to delve into the interviews of 408 women, evangelical and non-evangelical, in order to deepen and recognize the paths produced for remaking everyday life after experiencing the critical event called marital infidelity, to outline new questions and propose other developments in future research and approaches. Always with the intention of understanding so that science can be at the service of relieving social symptoms, without finding borders or taboos that prevent it from moving forward in promoting better relationships – religious or not